Kemampuan Menulis Gagasan, Pikiran, Pandangan, Arahan, atau Pesan Tertulis Teks Prosedur - Blongkod, Sri Winanda; Supriyadi, Supriyadi; Kadir, Herson (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research aims to describe the structure and rules of language in writing procedural texts for class VII students at MTs Muhammadiyah Gorontalo City in the 2023/2024 academic year using a quantitative descriptive approach. Based on the results of the analysis of the structure and language rules of procedural texts, it was found that out of a total of 43 students, there were 32 students who succeeded in achieving a score between 75-100, while 11 students obtained a score between 60-74 and did not meet the ability standards. Overall, the research results show that most of the seventh grade students at MTs Muhammadiyah Gorontalo City have good abilities in writing procedural texts.